Assessment of sunscreen usage among adults in the metropolitan area of Puerto Rico: implications for skin cancer prevention - Echevarria, Itzamar Pastrana; Cruz, Alicia Baez; Jimenez, Solianne Martinez; Lugo, Eneida De La Torre (International Journal of Research in Dermatology, 2025)
Background: Skin cancer incidence is rising in Puerto Rico. However, there is limited data on sunscreen knowledge and behaviors. This study evaluates these factors in Puerto Rico’s metropolitan area to identify barriers to effective sun protection and address a critical gap in the literature. Methods: A 31-question survey evaluated sunscreen behaviours, knowledge and perceptions among 205 adults in Puerto Rico’s metropolitan area. Participants were recruited via QR codes and clinic referrals, with data analyzed using descriptive statistics, Chi-square and t-tests with significance set at p<0.05. Results: While 83.41% acknowledged sunscreen’s role in preventing skin cancer, only 33.17% reported daily application. Among those who use sunscreen, 21.0% reported that they do not reapply it throughout the day. Additionally, 13.17% stated that timing of application does not matter as long as sunscreen is applied. Half of participants (50.24%) reported using an arbitrary amount instead of the recommended 1 ounce (approximately a shot-glass full) for full-body coverage. Females reported significantly higher daily use (39.74% vs. 14.81%, p=0.001) and greater concern about skin cancer all the time (40.40% vs 14.81%, p<0.0001). Younger adults had higher sunburn rates (84.62% vs. 50.88%, p<0.001) and more frequently identified the correct reapplication interval (48.35% vs. 23.68%, p<0.001). Conclusions: The study highlights critical gaps in sunscreen use and knowledge specific to Puerto Rico, particularly among younger adults and males. Targeted education on correct sunscreen uses and the risks of inadequate protection is essential to reduce the rising incidence of skin cancer in Puerto Rico.